ANALISIS REKRUTMEN & SELEKSI KARYAWAN BARU DI PT BARUNA DIRGA DHARMA, JAKARTA - Nurfarizki Nurfarizki; Narulita Syarweni; Dewi Winarni Susyanti (Epigram, 2019)
AbstractNurfarizki. The Analysis of the new employee recruitment & Selection Process at PT Baruna Dirga Dharma, Jakarta. 2018. The purpose of this research is to find out how the recruitment process is, to find out what factors influence the selection recruitment process, and the obstacles and solutions of the new employee barriers of PT Baruna Dirga Dharma. This research is a qualitative research. With a total of three informants, consisting of the Director, staff and HRD supervisors. Determination of informants is done by using purposive sampling technique. Data collection was carried out through observation, interviews, and documentation which were then analyzed qualitatively qualitative. The results show that the process is the factor in recruitment and selection, which begins with the planning of new employees, FPPK approved by the executive, and determining the source of recruitment. The selection process is selecting job applications, interview, psychotest, medical chech ups, offering letters, work agreements, filing & document records.Keywords: Recruitment, Selection, Human Resources.AbstrakNurfarizki. Analisis Proses Rekrutmen & Seleksi Karyawan Baru di PT Baruna Dirga Dharma, Jakarta. 2018. Tujuan penelitian ini adalah untuk mengetahui bagaimana proses rekrutmen, untuk mengetahui faktor-faktor apa saja yang mempengaruhi proses rekrutmen seleksi, dan hambatan serta solusi dari hambatan karyawan baru PT Baruna Dirga Dharma. Penelitian ini merupakan penelitian kualitatif. Dengan jumlah informan sebanyak tiga orang, terdiri dari Direktur, staf dan supervisor HRD. Penentuan informan dilakukan dengan menggunakan teknik Purposive Sampling. Pengumpulan data dilakukan melalui observasi, wawancara, dan dokumentasi yang kemudian dianalisis secara deskriptif kualitatif. Hasil penelitian menunjukan bahwa proses yaitu faktor dalam rekrutmen dan seleksi yaitu diawali dengan perencanaan karyawan baru, FPPK yang disetujui executive, dan menentukan sumber rekrutmen. Adapun proses seleksi yaitu menyeleksi lamaran kerja, interview, psikotest, medical chech up, offering letter, perjanjian kerja, filing & record dokumen.Kata Kunci: Rekrutmen, Seleksi, Sumber Daya Manusia.